Numerical and Experimental Investigation of Performance for Very-Low-Head Micro and Pico Kaplan Hydro-Turbines with Rim-Driven Generators - (:unkn) unknown (My University, 2020)
Renewable energy plays a significant role in new power generation worldwide, and hydropower is contributing to 86% of renewable electricity production within all other renewable energy resources. Simultaneously, hydropower shares 83% of U.S. renewable energy capacity and accounts for 77% of actual renewable electricity generation. However, most of the installed hydropower consists of large plants. Much potential hydro generation remains untapped, particularly at lower power and head levels. There is a substantial opportunity worldwide and across the U.S. in specific to add new hydropower generating capabilities at low-head sites such as non-powered dams, canals, and conduits with a water height of less than 30 meters, especially, where the potential of solar and wind is not available. As stated by the U.S. Department of Energy, there is an estimated potential hydropower capacity of 12,000 MW of the existed 80,000 unpowered dams with at least 3 feet of water head available. In this research, investigation of power-efficient micro and pico Kaplan hydro turbines at very-low-head with rim-driven generators to be studied and evaluated, specifically, at heads of less than 3 meters (10 ft). Optimization of performance and design for a 3D-printed conventional -with shaft- 7.6 cm (3-inch) Kaplan turbine to be carried out based on an experimental setup in the Hydro Turbines Laboratory of the University of Wisconsin-Milwaukee in addition to the utilization of Computational Fluid Dynamics (CFD). Then a shaftless rim-driven generator-based turbine (RDT) to be introduced and optimized. Such a new hydro turbine perception will increase the efficiency (of power generation) of hydro turbines in general, and the efficiency of low-head turbines in specific. The design optimization includes; the number of the blades for the turbine’s rotor (runner) and stator, the blade wrap-angle of the rotor, intake and draft tubes angles, lengths and shapes, and the guide vanes. The performance in terms of the power output and the efficiency is evaluated for the conventional turbine by utilizing CFD and by testing a 3D-printed model of the turbine in a custom-built experimental setup at different water heads (from 2.0 m to 2.6 m) and different rotational speeds (0 – 4000 rpm). The CFD setup is based on 3D transient turbulent featuring the Large Eddy Simulation (LES) model, and STAR-CCM+ is the CFD software. In addition, the high-performance computing (HPC) cluster of the University of Wisconsin-Milwaukee is used for solving the complex CFD simulations. To evaluate the advantage of the RDT over the conventional turbines, the rim-driven shaftless turbine is introduced in this research at the same boundary conditions. The RDT is not expected only to increase the efficiency of hydro turbines. It will also contribute saving the environment by allowing debris or fish to pass through the central area of the turbine, especially in the case of run-a-river hydro turbines applications. Furthermore, some applications of the RDT are presented in this study. The utilization of RDT in wastewater treatment plants (WWTPs) is one example where WWTPs usually have low or very-low head between the discharge point of the plant and the water body where the treated water is supposed to be disposed. At the same time, a significant continuous water flow rate is available all over the year for feasible hydro turbine installations. Such utilization will improve the energy efficiency of WWTPs.
Keywords: Hydro; Hydro-turbines; Hydropower; Renewable Energy; Rim-Drive Turbine; Water Turbines